2014
DOI: 10.1177/016146811411600601
|View full text |Cite
|
Sign up to set email alerts
|

Agency in Real Time? Situating Teachers’ Efforts toward Inclusion in the Context of Local and Enduring Struggles

Abstract: Background Teacher preparation for critical special education and inclusive education is premised on the ways in which dominant schooling discourses have unfairly positioned students with disabilities and their families. The hope of such teacher preparation programs is that through careful socialization into anti-oppressive discourses, teacher candidates will develop the capacity to go forth into troubled schooling systems and actively work against practices that perpetuate norms of dis/ability. Fundamental to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…This includes advocating for inclusive education through forming an inclusive teacher identity, and exerting personal autonomy to enact this identity (Li & Ruppar, 2020). It includes skills related to collective agency, in which allies are identified and sustained, with everyone taking a role in systems change (Naraian, 2014). It also includes recognizing ableism in its many forms.…”
Section: Implications For Teacher Educationmentioning
confidence: 99%
“…This includes advocating for inclusive education through forming an inclusive teacher identity, and exerting personal autonomy to enact this identity (Li & Ruppar, 2020). It includes skills related to collective agency, in which allies are identified and sustained, with everyone taking a role in systems change (Naraian, 2014). It also includes recognizing ableism in its many forms.…”
Section: Implications For Teacher Educationmentioning
confidence: 99%
“…In the current climate of social justice and equity, a growing body of research (Lyons et al, 2016 ; Naraian, 2014 ; Naraian & Schlessinger, 2018 ; Themane & Thobejane, 2019 ) emphasizes the agentic role of teachers in providing inclusive education and equitable atmospheres for marginalized students. Naraian ( 2014 ) for instance utilized a situated concept of agency to discover teachers’ activities in several schooling discourses via observation, interview, and document analysis. The results indicated that teacher education discourses that benefit the policy of inclusion vs. exclusion are not sufficient to fulfill the complex requirements of permitting the practice of inclusivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A body of burgeoning studies investigated teacher agency from various standpoints such as the impact of teacher agency on teachers' professional development and the general quality of education (Lai et al, 2016;Ruan, 2018), the effect of teacher reflection on teacher agency (Jones & Charteris, 2017;Reichenberg, 2022), the interplay between teacher agency and teacher identity (Buchanan, 2015;Connolly et al, 2018), teacher agency and identity commitment (Tao & Gao, 2017), the effect of curriculum reform on teacher agency (Poulton, 2020;Ruan et al, 2020), and the role of teacher agency in inclusive education (Lyons et al, 2016;Naraian, 2014;Naraian & Schlessinger, 2018;Themane & Thobejane, 2019). The data collection methodologies utilized in these studies for the teacher agency construct are mainly based on interviews, reflective essays or diaries, classroom observation, portfolios, focused group discussions, document analysis, and teachers' narratives.…”
Section: Introductionmentioning
confidence: 99%
“…In Italia, si è verificata una tendenza simile, che ha portato a sostituire il termine integrazione (processo volto a promuovere la partecipazione delle/degli studentesse/i con disabilità nella scuola di tutti), con il termine inclusione, interpretandone il significato in senso ampio, come processo che riguarda tutte/i le/gli studentesse/i, non solo coloro che sperimentano una condizione di disabilità (Lascioli, 2014). Il termine Inclusione scolastica assume infiniti significati sulla base delle culture e delle pratiche del contesto in cui si realizza (Naraian, 2014). Pertanto, appare ancora come un concetto ideale, lontano dalle pratiche d'inclusione (più o meno efficaci) introdotte a scuola (Naraian, 2020).…”
Section: Ta E Inclusione Scolasticaunclassified
“…L'analisi dei contributi ha fatto emergere gli elementi che ostacolano la TA inclusiva dei docenti, confermando i risultati del lavoro di Li e Ruppar (2020). In sintesi, essi sono: la disuguaglianza di status fra docente curricolare e di sostegno, l'assenza di pianificazione condivisa, la mancanza di adeguato supporto alle/i docenti da parte della struttura amministrativa e di governance della scuola, l'impossibilità di tradurre in pratica quanto appreso durante il corso di specializzazione, che conferisce la qualifica di special education teacher, l'impreparazione dell'insegnante di sostegno in alcuni specifici contenuti disciplinari, la mancanza di tempo dell'insegnante curricolare per la differenziazione a causa della necessità di completare i programmi e, infine, la pervasività della cultura abilista (Naraian, 2014;Naraian & Schlessinger, 2018). Questi elementi presenti nel contesto americano sono stati rilevati anche nel contesto italiano (Canevaro & Ianes, 2019;Ciambrone, 2018;Fiorucci, 2016;Santi & Ruzzante, 2016).…”
Section: Fattori Che Condizionano La Ta Inclusivaunclassified